Millennial-scale paleotemperature change in the Japan Sea during Marine Isotope Stage 3: Impact of meridional oscillation of the subpolar front - Sagawa, Takuya; Hasegawa, Takashi; Narita, Yusuke; Yokoyama, Masahiro; Kubota, Yoshimi; Okazaki, Yusuke; Goto, Akiko S.; Suzuki, Yoshiaki; Ikehara, Ken; Nakagawa, Takeshi (Palaeogeography, palaeoclimatology, palaeoecology, 2023)
The Japan Sea is a semi-closed marginal sea that has been significantly affected by fluctuations of the East Asian monsoon. Due to its geographic setting, the influence of the monsoon is significant especially during the last glacial period, when the low sea level stand restricted surface water exchange with adjacent seas. Millennial-scale change in the summer monsoon controlled the input of freshwater and nutrients into the Japan Sea during Marine Isotope Stage (MIS) 3, resulting in the deposition of alternating dark- and light-colored sedimentary layers. However, the relationships between the sediment color alternations and winter sea surface conditions, such as temperature and salinity, are not understood. Here, we provide high-resolution Mg/Ca-based winter sea surface temperature (SST) records during MIS3 from two sediment cores from the southern Japan Sea. The SSTs at both sites showed millennial-scale fluctuations with significantly different amplitudes. The southern site had a larger SST amplitude with warmer in dark- and cooler in light-colored intervals. The SST difference between the two cores was greater in dark-colored intervals. The millennial-scale changes in SST difference are probably attributable to meridional migration of the subpolar front, induced by winter monsoons and inflow of the Tsushima Warm Current, which had a northerly (southerly) position during interstadials (stadials). The results suggest that the millennial-scale winter monsoon variability contributed to sediment color alternation via greater cooling during stadials, which enhanced ventilation, in conjunction with the summer monsoon-induced productivity change. Therefore, both the winter and summer monsoons are key drivers of the oceanographic condition in the Japan Sea. •Millennial-scale oscillation of SST during MIS3 was revealed by Mg/Ca paleothermometry from the southern Japan Sea.•Millennial fluctuation of winter monsoon considerably affected meridional oscillation of subpolar front during MIS3.•Northward migration of the subpolar front during interstadials allowed TWC to influence along the southern Japan Sea.•Millennial-scale dark-light alternation of Japan Sea sediment is attributed to both East Asian winter and summer monsoons.